Inhibition of Histone Deacetylase-induced Myocardial Repair Is Mediated by c-kit in Infarcted Hearts - Zhang, Ling (American Society for Biochemistry and Molecular Biology, 2012)
Histone deacetylases (HDACs) play a critical role in the regulation of gene transcription, cardiac development, and diseases. The aim of this study was to test whether inhibition of HDACs induces myocardial repair and cardiac function restoration through c-kit signaling in mouse myocardial infarction models. Myocardial infarction in wild type Kit(+/+) and Kit(W)/Kit(W-v) mice was created following thoracotomy by applying permanent ligation to the left anterior descending artery. The HDAC inhibitor, trichostatin A (TSA, 0.1 mg/kg), was intraperitoneally injected daily for a consecutive 8 weeks after myocardial infarction. 5-Bromo-2-deoxyuridine (BrdU, 50 mg/kg) was intraperitoneally delivered every other day to pulse-chase label in vivo endogenous cardiac replication. Eight weeks later, inhibition of HDACs in vivo resulted in an improvement in ventricular functional recovery and the prevention of myocardial remodeling in Kit(+/+)mice, which was eliminated in Kit(W)/Kit(W-v) mice. HDAC inhibition promoted cardiac repairs and neovascularization in the infarcted myocardium, which were absent in Kit(W)/Kit(W-v) mice. Re-introduction of TSA-treated wild type c-kit(+) CSCs into Kit(W)/Kit(W-v) myocardial infarction heart restored myocardial functional improvement and cardiac repair. To further validate that HDAC inhibition stimulates c-kit(+) cardiac stem cells (CSCs) to facilitate myocardial repair, GFP(+) c-kit(+) CSCs were preconditioned with TSA (50 nmol/liter) for 24 h and re-introduced into infarcted hearts for 2 weeks. Preconditioning of c-kit(+) CSCs via HDAC inhibition with trichostatin A significantly increased c-kit(+) CSC-derived myocytes and microvessels and enhanced functional recovery in myocardial infarction hearts in vivo. Our results provide evidence that HDAC inhibition promotes myocardial repair and prevents cardiac remodeling, which is dependent upon c-kit signaling.